Pengaruh Pesan Kampanye Produk Kecantikan Terhadap Brand image di Media Sosial (Studi Kasus #BeautyHasNoGender di Akun Instagram @Dearmebeauty) - Claudia, Xena Sasa; Nathania, Debora Anggi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine whether the #BeautyHasNoGender campaign message on the @Dearmebeauty Dear Me Beauty Instagram account influences brand image. Explanatory quantitative research with survey data as a data collection method. The population in this study was 400 followers of the Instagram account @Dearmebeauty and was analyzed using simple linear regression. Hypothesis results show that the #BeautyHasNoGender campaign message dimensions influence brand image with a contribution of 48.1%.